LENIN, PETER I OF PROLETARIAT? - Muñoz Cabrejo, Fernando (2007)
When Lenin headed the October revolution in 1917 he wa.s guiding Russian proletariattowards the destruction of the old feudafistic regime and the incipient capitalism tocreate a new order which would mean the cancellation of inequity and social injustice.After sorne years, however, this objective was not achieved and instead the project of anew modern Europe emerged with a quite different goal: to transform the human beingin master of nature, a new condition which would enable him to mold it according tohis needs and whims. Maybe the known cry "Proletarians of the world, unite!" wouldchange into "Masters of Na tu re and Earth, unite!"